On the distribution of Verwey transition temperatures in natural magnetites. Issue 2 (28th October 2020) - Jackson, Mike J; Moskowitz, Bruce
SUMMARY: The Verwey transition in magnetite is a crystallographic phase transition occurring in the temperature range 80–125 K and depends on stoichiometry and cation substitution, which may in turn serve as an indicator of the conditions under which magnetite was formed or altered in nature. We have analysed the distribution of Verwey transition temperatures ( T V ) in a large set of samples ( N  = 1110) from a wide variety of rocks, sediments, and other natural and synthetic materials containing magnetite, mined from the database of the Institute for Rock Magnetism and from published studies. The analysis is restricted to measurements of remanence while warming through the transition from which T V was determined by the derivative method. Our analysis showed that the T V distribution exhibited a generally bimodal distribution of Verwey transition temperatures, both for the entire data set and for almost all of the lithological subsets. There is a sharp peak for values in the range 118–120 K, and a broad, relatively flat or polymodal distribution from about 98 to 118 K. The upper end of the distribution was sharp, with only a few values exceeding 124 K, and the tail on the lower end extended down to about 80 K. Virtually all of the sample types exhibited polymodal distributions, almost always with one peak near 120 K, and with one or more additional peaks at lower temperatures. Biogenic magnetites produced by magnetotactic bacteria had the lowest modal value of T V (100 K). Loesses (103.5 K) and igneous extrusives (102.5 K) also had low modal transition temperatures and distributions with dominant low- T V peaks. Lithological groups with the highest modal transition temperatures were modern soils (119.5 K), silicate minerals with exsolved magnetite (119 K) and sedimentary rocks (119 K). Numerical experiments confirmed that the derivative method for the determination of T V was reasonably robust and that the observed distributions cannot be explained as an artefact related to the determination of T V from individual thermomagnetic runs but rather is a general characteristic of natural magnetites. The results provide context for studies that interpret T V in particular samples in terms of natural processes or conditions during formation or alteration of magnetite.